Exocytosis of serotonin from the neuronal soma is sustained by a serotonin and calcium-dependent feedback loop - Leon-Pinzon, Carolina; Cercós, Montserrat G.; Noguez, Paula; Trueta, Citlali; De-Miguel, Francisco F. (Frontiers in Cellular Neuroscience, 2014)
The soma of many neurons releases large amounts of transmitter molecules through an exocytosis process that continues for hundreds of seconds after the end of the triggering stimulus. Transmitters released in this way modulate the activity of neurons, glia and blood vessels over vast volumes of the nervous system. Here we studied how somatic exocytosis is maintained for such long periods in the absence of electrical stimulation and transmembrane Ca2+ entry. Somatic exocytosis of serotonin from dense core vesicles could be triggered by a train of 10 action potentials at 20 Hz in Retzius neurons of the leech. However, the same number of action potentials produced at 1 Hz failed to evoke any exocytosis. The 20-Hz train evoked exocytosis through a sequence of intracellular Ca2+ transients, with each transient having a different origin, timing and intracellular distribution. Upon electrical stimulation, transmembrane Ca2+ entry through L-type channels activated Ca2+-induced Ca2+ release. A resulting fast Ca2+ transient evoked an early exocytosis of serotonin from sparse vesicles resting close to the plasma membrane. This Ca2+ transient also triggered the transport of distant clusters of vesicles towards the plasma membrane. Upon exocytosis, the released serotonin activated autoreceptors coupled to phospholipase C, which in turn produced an intracellular Ca2+ increase in the submembrane shell. This localized Ca2+ increase evoked new exocytosis as the vesicles in the clusters arrived gradually at the plasma membrane. In this way, the extracellular serotonin elevated the intracellular Ca2+ and this Ca2+ evoked more exocytosis. The resulting positive feedback loop maintained exocytosis for the following hundreds of seconds until the last vesicles in the clusters fused. Since somatic exocytosis displays similar kinetics in neurons releasing different types of transmitters, the data presented here contributes to understand the cellular basis of paracrine neurotransmission.